The Political in the Anthropocene: Reflections on a Ministerial Veto, 2021 - Rob Watts; Judith Bessant; Michelle Catanzaro; Philippa Collin; Stewart Jackson (Australian Journal of Environmental Education)
This article was prompted by a Ministerial veto (2021) of the Australian Research Council’s decision to fund a research project by the authors to explore the student-led climate movement in Australia. It was also prompted by criticism of the veto which accused the Minister of bringing “politics” into what was represented as a scholarly matter. It addresses two questions: How should we understand this idea of “politics” in the context of Australian climate politics since the 1990s? Secondly it considers dominant ways of thinking about “the political” devised by ancient Greek writers and politicians which still inform the European liberal tradition. We question how fit for purpose this approach is in the Anthropocene? Our key argument is that the western tradition of thinking about “the political” is deeply anthropocentric. Historical traditions have encouraged inegalitarian and anti-democratic accounts of who can be political by excluding different kinds of people from political life. The Anthropocene requires a new, critically reflexive account of “the political” that is inclusive of people currently marginalized and excluded as well as nonhumans and nonliving components of ecosystems on which we all depend. This extends the idea of democracy beyond the human and points to a politics of climate justice.